Refugees in Europe 1919-1959 A Forty Years' Crisis? - Frank, Matthew; Reinisch, Jessica (Bloomsbury Academic, 2017)
This volume offers a new history of Europe's mid-20th century as seen through the lens of its recurrent refugee crises. The editors conceive of the two post-war eras as a single 'forty years' crisis', enabling them not only to explore the continuities and disjunctures across the period but also to challenge established historiographical certainties and master narratives. The result is an indispensable research guide for students of migration, nationalism and international diplomacy in 20th-century Europe, and an up-to-date overview of current research for specialists.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: History / Europe; History; Electronic books